A Bispecific Antibody Composed of a Nonneutralizing Antibody to the gp41 Immunodominant Region and an Anti-CD89 Antibody Directs Broad Human Immunodeficiency Virus Destruction by Neutrophils - Duval, Mark (American Society for Microbiology (ASM), 2008)
In addition to the direct neutralization of virus, there is a broader potential for antibody-mediated inhibition of human immunodeficiency virus (HIV) by targeting HIV to effector cells. We demonstrate here that a bispecific antibody incorporating a broadly reactive anti-gp41 antibody, F240, and an anti-IgA receptor (CD89) antibody is effective at directing neutrophils to destroy HIV. Not only are neutrophils the predominant type of white blood cells and very efficient at mediating cell cytotoxicity, they are relatively resistant to infection with HIV. Therefore, they represent a significant weapon against infection if they can be directed and armed to destroy HIV and infected cells.